2020
DOI: 10.1002/anie.202005445
|View full text |Cite
|
Sign up to set email alerts
|

Al2Pt for Oxygen Evolution in Water Splitting: A Strategy for Creating Multifunctionality in Electrocatalysis

Abstract: The production of hydrogen via water electrolysis is feasible only if effective and stable catalysts for the oxygen evolution reaction (OER) are available. Intermetallic compounds with well‐defined crystal and electronic structures as well as particular chemical bonding features are suggested here to act as precursors for new composite materials with attractive catalytic properties. Al2Pt combines a characteristic inorganic crystal structure (anti‐fluorite type) and a strongly polar chemical bonding with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
1
20
0
1
Order By: Relevance
“… 120 Recently, Antonyshyn et al synthesized the intermetallic Al 2 Pt phase for efficient OER giving rise to a moderate η 10 of 450 mV that was better than the Pt reference. In addition to the activity, it showed a stable performance after activation during the first 100 h for more than 450 h. 108 …”
Section: Intermetallics For Oxygen Evolution Reactionmentioning
confidence: 93%
See 1 more Smart Citation
“… 120 Recently, Antonyshyn et al synthesized the intermetallic Al 2 Pt phase for efficient OER giving rise to a moderate η 10 of 450 mV that was better than the Pt reference. In addition to the activity, it showed a stable performance after activation during the first 100 h for more than 450 h. 108 …”
Section: Intermetallics For Oxygen Evolution Reactionmentioning
confidence: 93%
“… 106 It is a quite simple and straightforward technique and has widely been applied to attain various noble, i.e. PtDy, 107 Al 2 Pt 108 and non-noble metal-based, i.e. Ti 2 Ni, 87 TiCo 2 , 109 Ni 2 Ta 110 intermetallic compounds for HER and OER.…”
Section: Chemical Synthetic Strategies Of Intermetallicsmentioning
confidence: 99%
“…[ 63 ] For example, bulk intermetallic Al 2 Pt has been used as an electrocatalyst for OER. [ 64 ] It is shown that the near‐surface region underwent restructuring during OER operation, leading to surface oxidation and the formation of platinum and aluminum oxide. The presence of surface oxides leads to the blocking of active sites as well as the reduction of electrical conductivity, accounting for the reduced activity during long‐term operation.…”
Section: Structural Changes Under Reaction Conditionsmentioning
confidence: 99%
“…In addition, the alloying effect combining Pt with the main group element Al introduces a strong covalency into the chemical bonding, and thereby increasing the chemical stability. PtAl 2 with noticeable leaching of Al and formation of intermetallic Pt showed excellent oxygen evolution performance [12]. PtAl catalysts dealloyed from Pt 8 Al 21 alloy consisting of atomic-layer-thick Pt skin and Pt-Al intermetallic compound skeletons effectively enhanced ORR performance [13].…”
Section: Introductionmentioning
confidence: 98%